Associations between the workplace-effort in psychosocial risk management and the employee-rating of the psychosocial work environment – a multilevel study of 7565 employees in 1013 workplaces - Thorsen, Sannie Vester (Scand J Public Health, 2017)
Aims: This study examined the association between the workplace-effort in psychosocial risk management and later employee-rating of the psychosocial work environment. Method: The study is based on data from two questionnaire surveys – one including 1013 workplaces and one including 7565 employees from these workplaces. The association was analyzed using multi-level linear regression. The association for five different trade-groups and for five different psychosocial work environment domains was examined. Results: Limited but statistically significant better employee-ratings of the psychosocial work environment in the respective domains were observed among Danish workplaces that prioritized “development possibilities for employees,” “recognition of employees,” “employees influence on own work tasks,” good “communication at the workplace,” and “help to prevent work overload.” Conclusion: Danish workplaces with a high effort in psychosocial risk management in the preceding year had a small but significantly more positive rating of the psychosocial work environment by the employees. However, future studies are needed to establish the causality of the associations.